Anthrax Lethal Toxin Induces Acute Diastolic Dysfunction in Rats Through Disruption of the Phospholamban Signaling Network - Golden, Honey B. (2013)
BACKGROUND: Anthrax lethal toxin (LT), secreted by Bacillus anthracis, causes severe cardiac dysfunction by unknown mechanisms. LT specifically cleaves the docking domains of MAPKK (MEKs); thus, we hypothesized that LT directly impairs cardiac function through dysregulation of MAPK signaling mechanisms. METHODS AND RESULTS: In a time-course study of LT toxicity, echocardiography revealed acute diastolic heart failure accompanied by pulmonary regurgitation and left atrial dilation in adult Sprague-Dawley rats at time points corresponding to dysregulated JNK, phospholamban (PLB) and protein phosphatase 2A (PP2A) myocardial signaling. Using isolated rat ventricular myocytes, we identified the MEK7-JNK1-PP2A-PLB signaling axis to be important for regulation of intracellular calcium (Ca(2+)(i)) handling, PP2A activation and targeting of PP2A-B56α to Ca(2+)(i) handling proteins, such as PLB. Through a combination of gain-of-function and loss-of-function studies, we demonstrated that over-expression of MEK7 protects against LT-induced PP2A activation and Ca(2+)(i) dysregulation through activation of JNK1. Moreover, targeted phosphorylation of PLB-Thr(17) by Akt improved sarcoplasmic reticulum Ca(2+)(i) release and reuptake during LT toxicity. Co-immunoprecipitation experiments further revealed the pivotal role of MEK7-JNK-Akt complex formation for phosphorylation of PLB-Thr(17) during acute LT toxicity. CONCLUSIONS: Our findings support a cardiogenic mechanism of LT-induced diastolic dysfunction, by which LT disrupts JNK1 signaling and results in Ca(2+)(i) dysregulation through diminished phosphorylation of PLB by Akt and increased dephosphorylation of PLB by PP2A. Integration of the MEK7-JNK1 signaling module with Akt represents an important stress-activated signalosome that may confer protection to sustain cardiac contractility and maintain normal levels of Ca(2+)(i) through PLB-T(17) phosphorylation.